Bibliometric analysis and review of digital audit practices in the public sector of different countries - Ahmad @ Abdul Mutalib, Hawa; Mokhtar, Norsyahida; Ismail, Suhaiza (Institut Perakaunan Negara, Jabatan Akauntan Negara Malaysia, 2023)
The objectives of this paper are two-fold: first, it presents a bibliometric study on digital audit in the public sector of different countries; and Second, it provides review of prior studies on digital audit implementation by governments in various countries. There are two parts in the present study, and both use secondary data. The first part is a bibliometric study of past literature on digital audit in the public sector which was carried out to provide an overview of trend of publications over the last 30 years, citation analysis in terms of top cited journals and articles, as well as author analysis which covers most active single author and author with co-authorship and based on the country of the authors. The second part of the paper uses the content analysis technique on prior literature to extract and compile information on digital audit practices by the public sector of various countries in terms of the year of implementation, current status of implementation, and modules and the software used. The results of the first of the study indicate the increasing trend of publications on digital audit in the public sector which are authored by researchers from many countries. This implies the current trend of digital audit movement by governments around the world. For the second part, the review on digital audit practices of governments in different countries reveals several European countries such as Norway, Ukraine and Germany are championing digital audit in the public sector although none of the countries has full-fledged implementation. Most countries started with taxation audit, and are now having labs or incubators for full-fledged digital audit experimentation in the public sector.